Exploring students’ approach to learning tendencies among prospective biology teachers across years of study - Ika Nurani Dewi; Laras Firdaus (Biosfer: Jurnal Pendidikan Biologi, 2026)
Students’ Approaches to Learning (SAL) are widely recognized as critical determinants of educational quality and academic success. Despite their importance, empirical understanding of how students, particularly those in teacher education programs, adopt and develop these approaches remains limited. This study aims to investigate the learning approach tendencies among prospective biology teachers across different academic years. A total of 57 participants voluntarily participated in the study, comprising 24 first-year, 17 second year, and 16 third-year students enrolled in a biology teacher education program. The research employed a quantitative methodology to examine students’ preferences across four dimensions of learning approaches: deep motive (DM), deep strategy (DS), surface motive (SM), and surface strategy (SS). The findings indicate that third-year students exhibited a greater tendency toward deep learning approaches (DM and DS), suggesting a more intrinsic motivation and strategic engagement with learning materials. Conversely, first- and second-year students demonstrated a preference for surface learning approaches (SM and SS), which are typically associated with extrinsic motivation and superficial engagement. However, statistical analysis revealed that these differences were not significant, indicating that the year of study does not exert a substantial influence on the adoption of learning approaches. These results underscore the complexity of learning approach development and suggest that factors beyond academic progression may play a more pivotal role. Further research incorporating larger sample sizes and mixed method is recommended to elucidate the underlying mechanisms that shape students’ learning approach preferences over time.